Kompetensi Guru Pendidikan Agama Islam dalam Pengimplementasian Standar Proses (Studi Kasus di SMP Negeri 1 Kepahiang) - Levika Dian Anggraini; Zulkarnain Syapal; Zubaedi Zubaedi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
The problem in this study is how is the teacher’s competency in implementing the standard learning process for Islamic religious education at SMP Negeri 1 Kepahiang. The method used is descriptive qualitative, namely research that intends to describe in a systematic, factual and accurate manner the facts, situations or events and characteristics at SMP Negeri 1 Kepahiang. The respondents were PAI teachers and several students. The results of this study are: first, the standard implementation of the learning process for Islamic religious education at SMP Negeri 1 Kepahiang, Kepahiang Regency has been carried out, where students have been given the freedom to understand the subject matter with the guidance of the teacher. Second, the constraints in implementing process standards in learning Islamic religious education at SMP Negeri 1 Kepahiang, Kepahiang Regency after active learning is implemented in the form of 1) Lack of supporting facilities in the form of textbooks and learning media, 2) Learning media is not up to date or outdated, 3) Lack of student interest, and 4) Environmental factors and lack of attention from parents of students. There are four ways to provide solutions for solving the problems faced by Islamic Religious Education teachers by: 1) The teacher proposes to the school principal to want to add to the Islamic Religious Education package, at least in the book there is a ratio of 1: 3 in each teaching and learning process, 2) The teacher making teaching media using simple tools and materials in the form of cartons or available materials, 3) To arouse students’ interest by giving praise and giving satisfactory grades to students, and 4) Solutions to solve problems faced by Religious Education teachers Islam is to give understanding to parents that textbooks have a big influence on the teaching and learning process.